Impact of Blockchain Adoption, Regulatory Environment, and Institutional Investor Participation on FinTech Innovation - ALMESTAREHI, Ahmad Abdel Rahim; AL-ABABNEH, Hassan Ali; MALKAW, Eyad Mohammad (Theoretical and Practical Research in Economic Fields; Vol 16 No 2 (2025): TPREF, Volume XVI, Issue 2(34), Summer 2025DO - 10.14505/tpref.v16.2(34).01, 2025)
This study investigates how blockchain integration, regulatory policies, and the participation of institutional investors impact fintech innovation in Jordanian fintech companies. A descriptive analytical approach was used to evaluate and summarize the effects of these factors on innovation in the sector. An electronic survey was conducted among 125 administrative personnel working in Jordan's fintech industry. The results indicate a strong presence of blockchain adoption, involvement of institutional investors, and overall fintech innovation in these companies. However, the regulatory landscape in Jordan's fintech sector was found to be moderate. Furthermore, the analysis reveals that both blockchain integration and the regulatory framework significantly influence fintech innovation, with a significance level of 0.05. In light of these findings, the study suggests the creation of strategies to promote blockchain adoption, aiming to enhance efficiency and innovation in the industry.